Synchronous Polymorphous Adenocarcinoma and Canalicular Adenoma on the Upper Lip: An Unusual Presentation and Immunohistochemical Analysis - Ortega, Rose Mara [UNESP]; Bufalino, Andréia [UNESP]; Almeida, Luciana Yamamoto [UNESP]; Navarro, Claudia Maria [UNESP]; Travassos, Daphine Caxias [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Carlos, Roman; León, Jorge Esquiche (Springer Nature, 2018)
Multiple salivary gland tumors (MSGTs) are most common in the major than minor salivary glands. The most MSGTs are synchronous, either benign or malignant. A 61-year-old woman was referred presenting nine submucosal nodules, firm to fluctuant, being five nodules on the right side and four nodules on the left side of the upper lip. An incisional biopsy was performed. Hematoxylin and eosin staining was performed in 5-µm sections for histopathologic analysis. Immunohistochemical reactions were carried out in 3-µm sections in accordance with manufacturer’s instructions. The histopathological analysis showed focal area containing low-grade polymorphous adenocarcinoma (PAC) and multiple canalicular adenomas (CAs). Immunohistochemical analysis for each lesion was carefully investigated. Here, we present an unusual case of synchronous PAC and multiple CAs of the minor salivary glands, affecting the upper lip, which appears to be the first case showing PAC and CA.
Keywords: Canalicular adenoma; Minor salivary glands; Multiple salivary glands tumors; Polymorphous adenocarcinoma; Upper lip